Timuran Setia Industri Sdn Bhd / Sayyidati Hanum Helmi - Helmi, Sayyidati Hanum (Universiti Teknologi MARA, Perlis, 2023)
To finish off the requirement for my Bachelor's degree, I am honored to complete my internship as a Human Resource intern at Timuran Setia Industri Sdn Bhd, which is areliable one-stop online hardware store in Malaysia that satisfies your hardware needs.Timuran Setia Industri Sdn Bhd is recognize themselves as specialist which specialize inproviding solution. As an intern, I carried out a lot of roles such as in HR Department, I carried out my roles as HR assistant which I assist in key in leave application form, payroll pending for commission, advances deduct, overtime and leave. In addition, during my intern at Timuran Setia Industri I am also carried out my roles in Financial department as account assistant. I have been assisted in checking and verify bank, credit card transaction, generate invoice and payment voucher. I am completing this task not just for the company's headquarters but also for its branches. My objective for this internship is to analyze SWOT and PESTEL analysis. After analyzing the SWOT and PESTEL analysis, I must give recommendations for each of the strengths, weaknesses, opportunities, and threats that I discuss in the report. By making these findings, it will provide a complete picture of the company's internal strengths and weaknesses and external opportunities and threats. By evaluating these elements, the company can create a plan to take advantage of opportunities, increase vulnerabilities, reduce threats, and increase its competitiveness and business goals. In conclusion, doing my internship at Timuran Setia Industri give me a give me a lot ofexperience and benefit which sharpen my skills to do best in this industrial practice. Forinstance, sharpen my skill in computing, time management and using company’ssoftware. My supervisor taught me a lot of this and as an intern I will not give up inlearning new things because new things give me a lot of moral value.